| - Yoshii, Koji; Ito, Kiyoshi; Miyamachi, Hiroki; Kanao, Masaki (National Institute of Polar Research, 2004)
P(論文) Large seismic explosion experiments were conducted on the traverse route from Syowa to Mizuho Stations by the 41st Japanese Antarctic Research Expedition (JARE-41) in 1999-2000 and JARE-21 in 1980-1981. The P-wave velocity structure of the ice sheet, the crust and the uppermost mantle in the Mizuho Plateau, East Antarctica, is deduced from travel-time analysis of the combined data of refractions and wide-angle reflections. The ice sheet has a surface layer 60-100 m in thickness with P-wave velocity of 2.34 - 3.01 km/s, while the deeper part has a P-wave velocity of 3.80 - 3.85 km/s. There is a v-shaped valley with a drop of 600 m in the basement topography at the middle of the profile line; this is consistent with the variations of the ice-sheet flow. The uppermost crust has a P-wave velocity of 6.17 - 6.20 km/s on the coastal side, 6.08 km/s under the above mentioned v-shaped valley and 6.21 - 6.26 km/s on the inland side. The middle and the lower crustal P-wave velocities are 6.45 and 6.56 km/s, and their thicknesses are about 10 and 20 km, respectively. The Moho boundary is almost 40km deep with a gentle dip toward the inland direction with a Pn velocity of 8.03 km/s. The Vp/Vs value of 1.70 for the entire crust is derived from S-wave travel-time analysis. Moreover, calculated gravity anomalies, based on the obtained velocity structure and a density-velocity relation obtained in the laboratory experiments, coincide well with observed anomalies, but there are some misfits at the v-shaped valley of the basement rock and around the S-1 and S-6 shot points at both ends of the profile. Compared with the results from high pressure laboratory measurements of velocities for metamorphic rocks, it is implied that felsic gneiss is possibly dominant in the uppermost crust along the Mizuho traverse route and that the basement layer with a P-wave velocity of 4.69 km/s near the coast and the v-shaped valley may be a mixture of ice with sand or stone. departmental bulletin paper